(untitled) - House, J. E. (Amsterdam, 2008)
Inorganic Chemistry provides essential information in the major areas of inorganic chemistry. The author emphasizes fundamental principles―including molecular structure, acid-base chemistry, coordination chemistry, ligand field theory, and solid state chemistry ― and presents topics in a clear, concise manne
Keywords: Chemistry, Inorganic,Hóa học vô cơ; Textbooks,Sách giáo khoa